FPGAs world class designs. - Maxfield, Clive, ....- (Amsterdam : Elsevier, 2009)
Table of Contents Ch. 1 Alternative FPGA Architectures Ch. 2 Design Techniques, Rules, and Guidelines Ch. 3 A VHDL Primer: The Essentials Ch. 4 Modeling Memories Ch. 5 Introduction to Synchronous State Machine Design and Analysis Ch. 6 Embedded Processors Ch. 7 Digital Signal Processing Ch. 8 Basics of Embedded Audio Processing Ch. 9 Basics of Embedded Video and Image Processing Ch. 10 Programming Streaming FPGA Applications Using Block Diagrams In Simulink Ch. 11 Ladder and functional block programming (online) Ch. 12 Timers (online)